Palmcrete lintel / Muhammad Izham Irwan and Sallehan Ismail - Irwan, Muhammad Izham; Ismail, Sallehan (2024)
Sustainability is increasingly crucial in concrete construction as awareness of environmental degradation and climate change grows. The conventional method of producing concrete is notorious for its significant release of greenhouse gases, particularly carbon dioxide from cement manufacturing. Furthermore, palm oil mill effluent poses environmental risks, contaminating air and water, and impacting human health with respiratory and cardiovascular issues. This study investigates the potential of oil palm shells (OPS) as lightweight aggregates in concrete, varying the OPS percentages to optimise mechanical strength and workability. The objectives include determining the optimal OPS ratio in mix designs for adequate mechanical strength, assessing workability through OPS replacements with acceptable water absorption rates, and identifying the benefits of utilizing OPS waste in construction. Field experiments in a concrete lab analysed four OPS specimen variations to enhance both strength and workability. Moulds with different OPS percentages were fabricated using iron casts and other materials. Tests measured compressive strength, flexural strength, water absorption, and ultrasonic pulse velocity. Results highlighted the mix design's significant role in achieving strength, lightweight properties, and sustainability simultaneously. Oil palm shells, as a byproduct of the palm oil industry, offer promise in construction due to their lightweight nature, heat insulation properties, and environmental benefits. This study evaluates their practicality and commercial viability, specifically in precast lightweight concrete lintels, underscoring their potential contribution to sustainable building practices.